The association between atorvastatin administration and plasma total homocysteine levels in renal transplant recipients - Ali Monfared; Seyyede Zeinab Azimi; Ehsan Kazemnezhad (Society of Diabetic Nephropathy Prevention, 2016)
Background: Statins improve prognosis in patients with coronary heart diseases by decreasing the incidence of vascular events. Excess prevalence of hyperhomocysteinemia, an independent risk factor of cardiovascular diseases, has been observed in stable renal transplant recipients (RTRs). Objectives: The objective of our study was to evaluate the association between atorvastatin administration and plasma total homocysteine (tHcy) levels in RTRs. Patients and Methods: We performed a retrospective cross-sectional study in 148 cyclosporine A (CsA) treated stable RTRs. We compared tHcy level and other demographic and clinical variables in RTRs with and without atorvastatin. Results: 58.1% of the 148 RTRs were treated with atorvastatin (20-40 mg/day). Mean tHcy levels were lower in patients treated with atorvastatin compared to nonusers (14.80 ± 5.13 µmol/l versus 16.95 ± 7.87 µmol/l, P = 0.04). The comparison of 85 patients treated with atorvastatin and 61 non-users revealed that those subjects with atorvastatin were older, with higher estimated creatinine clearance and elevated body mass index (BMI). They were more likely to have higher systolic blood pressure and CsA trough level (C0). The association between lower tHcy levels and atorvastatin use was confirmed in the multivariate regression model (P = 0.004). However tHcy levels were independently and negatively associated with serum folate (P = 0.0001) and vitamin B12 levels (P = 0.001) and positively with serum BUN (P = 0.001) and diastolic blood pressure (P = 0.024) as well. Conclusions: These data support the association between lower tHcy levels and atorvastatin administration in RTRs. Further clinical trials are recommended to clarify homocysteine lowering effect of atorvastatin.